RNA methodologies laboratory guide for isolation and characterization - Farrell, Robert E. Jr (Academic Press, an imprint of Elsevier, 2017)
This book is a collection of tried and tested laboratory protocols for the isolation and characterization of mammalian RNA. It studies cellular regulation using RNA as a parameter of gene express, offers RNA isolation strategies, and explains proper handling, storage, and manipulation of RNA. -- Provided by publisher.